THU0047 Baff and B2m, but not Free Light Chains, Correlate with Disease Activity in Primary SjÖGren's Syndrome (PSS). (10th June 2014) - James, K.; Cockell, S.J.; Gillespie, C.S.; Assi, L.; Bowman, S.; Griffiths, B.; Ng, W.-F.
Abstract : Background: Both kappa and lambda free light chain (FLC) levels appear to be elevated the serum of patients with pSS, in comparison to healthy controls [1, 2]. Consequently, FLCs may represent potential biomarkers for disease activity in pSS. Objectives: To investigate the relationship between kappa and lambda serum levels and disease activity in the UK primary Sjögren's syndrome registry (UKPSSR), a cohort of clinically well-characterised patients and healthy controls [3]. Methods: Serum samples for 599 pSS patient and 287 healthy controls were tested using the Freelite (kappa and lambda), BAFF, and B2M assays, and using Combylite, a new assay of both kappa and lambda chains in a single test. Additional subjective and objective clinical data, including ESSDAI, ESSPRI and immunological markers, were retrieved from the UKPSSR database [3]. Comparison of baseline patient and controls FLC levels was by ANOVA. Pearson correlation coefficients were calculated for patient characteristics and serum levels. Multivariate logistic regression analysis was performed to determine independent predictors for ESSDAI. All statistical analyses were performed in R [4]. Results: Both the kappa and lambda FLC levels, and the Combylite combined FLC level, were significantly higher in pSS patients in comparison with the healthy controls. Of the 599 patients, 339 (57%) had abnormal FLC levels (high kappa, high lambda or abnormal kappa:lambda ratio). The three FLC levels were all significantly correlated with one another. In addition the FLC levels correlated significantly with a number of clinical factors, including B2M, IgG and average Schirmer's but not with BAFF levels, age or disease duration. The kappa free light chain levels had higher correlations with clinical data than the lambda in the majority of cases, with the combined Combylite scores falling between the two in most cases. Multivariate analysis indicated that BAFF and B2M are independent predictors of ESSDAI score, while FLC levels are not. Conclusions: The combined Combylite assay produces a FLC measurement that is comparable with the separate kappa and lambda assays. Serum FLC levels are increased in patients with pSS in comparison with healthy controls and correlate with several clinical factors. However, multivariate analysis indicates that BAFF and B2M, but not FLC levels, are predictors of disease activity. References: Gottenberg JE, Seror R, Miceli-Richard C, et al. PLoS One 2013; 8(5): e59868. Gottenberg JE, Aucouturier F, Goetz J, et al. Ann Rheum Dis 2007; 66(1): 23-7. Ng WF, Bowman SJ, Griffiths B, et al. Rheumatology (Oxford) 2011; 50(1): 32-9. R Core Team, R Foundation for Statistical Computing. 2013 http://www.R-project.org Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.4986